Immunometabolic disorders in the pathogenesis of systemic lupus erythematosus - Tokarska, Kamila; Majsterek, Ireneusz; Cuchra, Magda; Woźniacka, Anna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2019)
Systemic lupus erythematosus is a chronic autoimmune disease connected with complex and unclear disorders of the immune system, which causes inflammation of body tissues and internal organs. It leads to the formation of anti-nuclear antibodies (ANA) and immune complexes. Numerous immune system disorders and dysfunctions in the biochemical processes can occur in the course of the disease, and a wide range of abnormalities associated with cellular respiratory processes and mitochondrial function have been documented. The following paper presents the current understanding of the contribution of these disorders to the pathogenesis of lupus.